البنية السردية في الحديث النبوي: دراسة تحليلية في كتاب "صحيح القصص النبوي من ١-٥٠" لأبي إسحاق الحويني الأثيري - نور شفاء نعيمة محمد نصر الدين
Narrative hadiths are one of the most widely used methods of prophetic preaching in coveying the revelation of Allah to him, these hadiths are also a valuable type of prose in Islamic Literature and contemporary Arabic stories. The study of The Narrative Structure in Hadith of the Prophet: an analytical study in the book Authentic Prophetic Tales (Sahih Al-Qasas Al-Nabawi) from 1-50 by Abu Ishaq Al-Huwaini Al-Athiri aims to identify narrative themes in the prophetic stories, study the vision of the narrative and analyze the narrative structure in twenty stories of the authentic hadiths selected from the book, which tells the stories of the prophets and messengers. The author adopted two approaches: the descriptive approach to describe the subject of the story and the analytical approach to analize the elements of the narrative structure of each story, and to note the narrative vision that it included through the narrative, considering the context of speech and situation. The findings of this study indicate that these hadiths can be categorized into interesting narratives from the aspect of the use of varied narrative techniques and structures from dialogue, descriptive, events, characters, time, place, and themes of the story to captivate the readers without ignoring the important educational aspects and lessons conveyed.